Review papersRole of Toll-like receptors in the development of allergic inflammation in asthma - Oleś, Dominika; Szczepankiewicz, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
Toll-like receptors (TLR) are a family of receptors that play an important role in innate immune response. Their presence has been confirmed in macrophages, dendritic cells, neutrophils and mast cells. Toll-like receptors receptors recognize microbial products and their activation triggers the innate immune response mechanism. They can also participate indirectly in the adaptive immune response. Allergic asthma is a chronic inflammatory disease with characteristic clinical symptoms including airway hypersensitivity, airway obstruction and wheezing. Airway inflammation is related to eosinophilia, elevated levels of inflammatory mediators and excessive mucus secretion. In animal models it has been shown that Toll-like receptors, because of their role in immunological processes, may be an important therapeutic target in asthma.